A QUALITATIVE INVESTIGATION INTO MALDIVIAN PARENTS’ COPING MECHANISMS FOR BRINGING UP CHILDREN WITH AUTISM SPECTRUM DISORDER - Aishath Naziya Niyaz; Niuma Mohamed (LIFE: International Journal of Health and Life-Sciences, 2025)
The mental and emotional health of their parents may be greatly impacted by the social interaction, communication, and behaviour difficulties that children with autism spectrum disorder (ASD) frequently experience. Compared to parents of children with other disabilities or children who are typically developing, parents of children with ASD often experience higher levels of stress, depression, and anxiety. Many people therefore use a variety of coping mechanisms to deal with these difficulties. The purpose of this study was to investigate the coping strategies employed by Maldivian parents of children with ASD. Thirteen parents were chosen through purposive sampling, and researchers interviewed them in-person using a descriptive qualitative methodology. In order to guarantee consistency and dependability in the coding and theme development, a collaborative team approach was utilised in conjunction with thematic analysis to interpret the data. The results showed that parents employed both emotion-focused tactics, like acceptance and adaptation, and problem-focused tactics, like enhancing communication, managing daily routines, and looking for social support. These coping strategies improved parents’ mental health and their kids’ behaviour while assisting them in navigating the psychological costs of providing care. The findings emphasise how crucial it is to offer families of children with ASD competent support. Healthcare providers are urged to evaluate coping mechanisms used by parents and design interventions that consider these families’ background. Parental stress reduction and the general well-being of their children can be greatly enhanced by offering suitable resources, such as support groups, educational materials, online platforms, and referrals to professional services like social work or therapy. In addition to helping parents on their journey of providing care, these insights improve the care given to children with ASD and strengthen parent-child bonds.